Determinan Stock Price: Studi Empiris pada Perusahaan Properti dan Real Estat - Diah Kusuma Wardhani; Henny Mulyati (Jurnal Akuntansi dan Governance, 2021)
This study is conducted to analyze the determinant of stock price simultaneously and partially in Property and Real Estate (RE) Exchange in 2014-2019. The type of this research used quantitative with the causal associative method. The use of purposive sampling technique is in accordance with the criteria for determining the research sample. The finding of the research shows that leverage, profitability, and market value simultaneously affect the stock price by 44,6% as well as partially effect stock price with a value of 248.159 on DER, 1066.566 on NPM, and a value of 19.922 on PER.